RADISH FISHING WEBSITE DESIGNING USING MACROMEDIA DREAMWEAVER 8.0, PHP AND MYSQL - Mohamad Tamrin; Aqwam Rosadi Kardian,S.kom.,MMSI (Jurnal Sistem Informasi, 2008)
Growing computer technology so that all things computer problems can be solved with one participant registration fishing with the use of race registration website design participants of an online fishing contest. With the design of this website make it easier for fans to know about fishing lure Radish and can provide or obtain information necessary for angler.